2021
DOI: 10.1017/s0022149x2000098x
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profile in patients with cystic echinococcosis and identification of possible cellular pathways

Abstract: Cystic echinococcosis (CE) is a neglected tropical disease, caused by metacestode (larval) form of the Echinococcus granulosus sensu lato (sl) in humans. MicroRNAs (miRNAs) are small, stable, tissue-specific RNA molecules encoded by the genome that are not translated into proteins. Circulating miRNA expression profiles vary in health and disease. The aim of this study is to determine the altered cellular pathways in CE by comparing the miRNA profiles of controls and CE patients with active or inactive cysts. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The candidate markers identified in this work were not detected in previous sRNA high-throughput studies of human CE [45,46] since different sample type (e.g., blood), technology and/or analysis criteria were used. In the mentioned articles, PCR arrays were employed and thus, results were dependent on the composition of each selected plate, where a limited number of miRNAs were amplified.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The candidate markers identified in this work were not detected in previous sRNA high-throughput studies of human CE [45,46] since different sample type (e.g., blood), technology and/or analysis criteria were used. In the mentioned articles, PCR arrays were employed and thus, results were dependent on the composition of each selected plate, where a limited number of miRNAs were amplified.…”
Section: Discussionmentioning
confidence: 97%
“…Contrarily, in CE patients, no parasite miRNAs were detected. Previously, high throughput characterizations of the profiles of circulating sRNAs were performed in experimental AE [43], experimental CE [44], and human CE [45,46]. However, parasite miRNAs were only studied in the AE experiment where authors inoculated mice with protoscoleces and identified 7 circulating miR-NAs which did not include emu-miR-87-3p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study investigating the miRNA expression profile differences between CE patients and healthy controls revealed that the identified miRNAs were related to cell proliferation, apoptosis, cell-cell interactions, and the cell cycle. The decrease in the expression of these miRNAs in CE patients suggested that CE may play a regulatory role in the anti-cancer effect through miRNA regulation [ 31 ]. To date, many mechanisms have been suggested for CE-related anti-cancer effects, including parasite molecules and activation of host immune response [ 1 ].…”
Section: Discussionmentioning
confidence: 99%